Environmental Impact Assessment of Road construction in Afghanistan (A case study of Jalalabad city) - Zalmay khaliqi; kaiwaan abdulhai; Mohammad Ajmal Stanakzai (Revista Eídos)
Development activities are often associated by significant environment impact, either directly or indirectly. Environmental Impact Assessments (EIAs) are critical tools used to identify, evaluate, and mitigate these impacts prior to implementing development projects. This study highlights the consequences of neglecting EIA processes in Afghanistan, with a specific focus on the second lane development of Daronta Road on the Kabul-Jalalabad highway. Through observational and questionnaire-based surveys, the study identifies key environmental and socio-economic issues, including the destruction of approximately 5,096 square meters of land, loss of agricultural areas, private properties, and vegetation, as well as increased air and noise pollution. The findings reveal that 138 trees were removed, infrastructure such as irrigation systems was destroyed, and affected communities faced unmet compensation promises. The study underscores the critical need for integrating EIA into the decision-making process to achieve sustainable development. Recommendations include strengthening public awareness, enforcing existing EIA policies, and prioritizing environmental considerations in future projects.